2014
DOI: 10.2310/8000.2013.130860
|View full text |Cite
|
Sign up to set email alerts
|

Ineffectiveness of cognitive forcing strategies to reduce biases in diagnostic reasoning: a controlled trial

Abstract: Objectives: Cognitive forcing strategies (CFS)may reduce error arising from cognitive biases. This is the first experimental test to determine the effect of CFS training in medical students. Methods: Students were allocated to CFS training or control during a 4-week emergency medicine rotation (n = 191). At the end of the rotation examination, students were tested using computer-based cases. Application of CFS could enable reduction of diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 24 publications
(35 reference statements)
2
89
0
Order By: Relevance
“…9,10 However, interventions directed at reducing errors by making clinicians aware of cognitive biases have been negative. 14,15 It may well be that there is no Bquick fix^to reduce errors, and strategies should be directed at improving formal and experiential knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 However, interventions directed at reducing errors by making clinicians aware of cognitive biases have been negative. 14,15 It may well be that there is no Bquick fix^to reduce errors, and strategies should be directed at improving formal and experiential knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…2,3,[8][9][10] However, the available scientific evidence does not support this strategy. [14][15][16][17][18][19] Critically, a series of experiments demonstrated that instructing residents to proceed slowly and cautiously when diagnosing written medical cases did not improve diagnostic accuracy compared to being instructed to be more rapid. [16][17][18][19] In another study, participants had improved diagnostic accuracy after receiving a warning about the extreme difficulty of written medical cases compared to participants who did not receive the same warning; however, the authors were not able to replicate this effect with new cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is very little empirical evidence that this is effective and it is therefore controversial. 26,27 However, it might be argued that this is 'the best model we have' at present. A variety of educational techniques to improve clinical reasoning have been researched in general medicine and surgery with mixed results.…”
Section: Decision-makingmentioning
confidence: 99%
“…Indeed, for both control and interventional arms of one CFS study, diagnostic accuracy was inversely related to the time spent on the diagnosis. 58 In contrast, a series of studies conducted by Mamede have shown that structured reflectionsystematically listing the supportive, contradictory, and absent findings of an initial and alternate diagnoses for a written case-improved both learning and categorization of illness scripts in medical students. 59 The reflective intervention was similarly tested in internal medicine residents where it has some success in overcoming availability bias and improving diagnostic accuracy.…”
Section: Cognitive Forcing Strategiesmentioning
confidence: 99%
“…Both uncontrolled and controlled studies have failed to demonstrate clinically or mathematically significant degrees of improvement following this type of intervention. [56][57][58] One interpretation of the results is that the experimental subjects (all students) may not necessarily use non-analytic processing as a primary decision strategy, and if using System II, a "ceiling effect" may exist where further analysis may fail to improve accuracy. Indeed, for both control and interventional arms of one CFS study, diagnostic accuracy was inversely related to the time spent on the diagnosis.…”
Section: Cognitive Forcing Strategiesmentioning
confidence: 99%